The Same Old Arguments: Tropes of Race and Class in the History of Prostitution from the Progressive Era to the Present - Lilley, Terry G. (Social justice, 2019)
The article discusses the interconnection of race and social class in the history of prostitution from the progressive era to 2019. Also cited are how the policies and practices to prevent prostitution systematically ignored structural factors, how criminal justice strategies against sex work discriminated marginalized groups and communities of color, and the works of Katharine Bement Davis in U.S. women's corrections and social reform.